Smoking practices in jordanian people and their impact on semen quality and hormonal levels among adult men - Al-Matubsi, Hisham Y; Kanaan, Reem A; Hamdan, Farqad; Salim, Maher; Oriquat, Ghaleb A; Al-Hanbali, Othman A (Central European Journal of Public Health, 2011)
Despite worldwide anti-smoking campaigns, cigarette smoking prevalence is increasing in the third-world countries. It is now regarded as the most important public health issue. Here, we study the current smoking situation and investigate the impact of cigarette smoking on semen quality and hormonal levels among adult people. Furthermore, we suggest various strategies to reduce smoking consumption among young individuals. A cross-sectional data from 804 adult smoker subjects (male n=530 and female n=274) aged between 15 and 45 years were analyzed. One hundred and eleven males were agreed for further evaluation of their semen quality and hormones compared with 93 age-matched non-smoking males. This study showed that the major factors initiating smoking among women were friends' influence (49%), life pressures (16%) and parental imitation (14%). The major reasons in men was friends' influence (65%). Furthermore, 61% of women and 89% of men smoke in public implying social acceptance or even en-couragement of this habit. This study also found that low-income Jordanians consume more tobacco materials than those in the middle- and higher income. Furthermore, smokers had significantly lower (p<0.001) sperm concentration and motility values and higher (p<0.001) serum testosterone and luteinizing hormone (LH) levels than non-smokers.
Keywords: dospělí; Smoking; Female; Jordánsko; Luteinizing Hormone; Adult; mladý dospělý; ženské pohlaví; průřezové studie; Peer Group; Semen; testosteron; Adolescent; kouření; lidé; sperma; vyrovnaná skupina; Cross-Sectional Studies; Male; Social Environment; sociální prostředí; Socioeconomic Factors; Young Adult; luteinizační hormon; lidé středního věku; Testosterone; socioekonomické faktory; mužské pohlaví; Jordan; Middle Aged; mladiství; Humans